2013
DOI: 10.1007/s13593-013-0150-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of composted biochar on plant growth and soil fertility

Abstract: International audienceMankind is actually facing serious issues due to the overexploitation of fossil fuels, biomass, soils, nitrogen, and phosphorus. It is claimed that biochar addition to soil improves C sequestration to prevent CO2 from atmospheric cycling. Biochar addition should also increase soil fertility in a similar way as anthropogenic dark earths of Central Amazonia. Previous studies have shown that biochar stimulates plant growth and increase fertilizer efficiency, especially when biochar is combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
159
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(188 citation statements)
references
References 32 publications
23
159
1
5
Order By: Relevance
“…The application of WB, in combination with complementary annual N fertilization and fresh organic matter (added via crop residues) seem to be the key components to build up soil organic matter in the clay soil. Liu et al (2012a) and Schulz et al (2013) reported the importance of combining biochar with organic fertilization or composting biochar to improve soil fertility. Schmidt (2008) argues that biochar is not a fertilizer, but rather a nutrient carrier and a habitat for microorganisms and that it has to be charged first to be biologically active and efficient in soil-enhancing properties.…”
Section: Determining Factors and Potential Effects Of Biochar On Soilmentioning
confidence: 99%
“…The application of WB, in combination with complementary annual N fertilization and fresh organic matter (added via crop residues) seem to be the key components to build up soil organic matter in the clay soil. Liu et al (2012a) and Schulz et al (2013) reported the importance of combining biochar with organic fertilization or composting biochar to improve soil fertility. Schmidt (2008) argues that biochar is not a fertilizer, but rather a nutrient carrier and a habitat for microorganisms and that it has to be charged first to be biologically active and efficient in soil-enhancing properties.…”
Section: Determining Factors and Potential Effects Of Biochar On Soilmentioning
confidence: 99%
“…Hasil ini relatif sejalan dengan yang dilaporkan oleh Abujabhah, Bound, Doyle, & Bowman (2016), bahwa pemberian arang hayati 47 ton ha -1 nyata meningkatkan C-organik dalam tanah sebesar 23% (dari 2,19% menjadi 2,69%), tetapi peningkatan ini masih lebih rendah bila dibandingkan dengan perlakuan kompos 10 ton ha -1 , yaitu sebesar 55%. Peningkatan C/N media pembibitan akibat pemberian arang kayu sengon dan pupuk organik berpotensi menyebabkan proses imobilisasi N. Upaya yang dapat dilakukan untuk menghindari pengaruh negatif proses imobilisasi N terhadap tanaman adalah melakukan pemupukan N untuk memenuhi kebutuhan tanaman (Schulz, Dunst, & Glaser, 2013).…”
Section: C/n Ratio In Seedling Media Influenced By: (A) 10% Organic unclassified
“…compost, manure, digestate etc. ), a potentially attractive tool to improve agricultural productivity (Schulz et al 2013(Schulz et al , 2014Prost et al 2013;Liu et al 2013). Recently, Joseph et al (2013) and Novak and Busscher (2013) introduced tailor-made and designer biochars having specific properties adapted to their potential use.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Joseph et al (2013) and Novak and Busscher (2013) introduced tailor-made and designer biochars having specific properties adapted to their potential use. Despite the uncertainty about exact mechanisms of improvement, biochar has been most successful at improving crop yields on highly weathered soils (Crane-Droesch et al 2013;Liu et al 2013;Schulz et al 2013;Jeffery et al 2011;Lehmann and Rondon 2006;Cornelissen et al 2013;Obia et al 2016). Highly weathered soils are typical for humid (e.g.…”
Section: Introductionmentioning
confidence: 99%